Types And Populations of Pests on Cabbage Plants Which Are Planted Intercropping with Mustard Greens Refugia - Wanta, Noni N.; Dumalang, Sherlij; Paat, Frangky J.; Paruntu, Meisye H. B. (Sam Ratulangi University, 2025)
The purpose of this study is to determine the types and populations of pests in cabbage plants planted intercropping with mustard greens in Kakaskasen I Village, Tomohon City. The research method used is a survey method on experimental land made without the use of pesticides. Data collection was carried out on 3 observation plots with the number of sample plants in each plot was 30 plants. Observation of pest types and populations on cabbage plants is carried out every 2 weeks from the age of cabbage plants 2 weeks after planting to harvest. The data obtained were analyzed descriptively about the types and populations of pests in cabbage plants. The results of this study found that the main pests that attack cabbage plants that are planted intercropped with mustard greens are Plutella xylostella and Crocidolomia binotalis. The population of P. xylostella pests in cabbage plants is low on average ranging from 0.002 to 0.067 larvae/plant, while the population of C. binotalis pests is high with an average range of 0.056 to 1,422 larvae per plant. It is necessary to preserve the parasitoid D. semiclausum to control the pest of P. xylostella and find environmentally friendly pest control solutions of C. binotalis to produce healthy cabbage production. Keywords: Cabbage, Mustard greens, Population, Pests, Parasitoid Abstrak. Tujuan dari penelitian ini adalah untuk mengetahui jenis dan populasi hama pada tanaman kubis yang ditanam tumpangsari dengan refugia sawi hijau di Desa Kakaskasen I Kota Tomohon. Metode penelitian yang digunakan adalah metode survei pada lahan percobaan yang dibuat tanpa menggunakan pestisida. Pengambilan data dilakukan pada 3 plot pengamatan dengan jumlah tanaman sampel masing-masing plot adalah 30 tanaman. Pengamatan jenis dan populasi hama pada tanaman kubis dilakukan setiap 2 minggu sekali sejak tanaman kubis berumur 2 minggu setelah tanam sampai panen. Data yang diperoleh dianalisa secara deskriptif tentang jenis dan populasi hama pada tanaman kubis. Hasil penelitian ini ditemukan hama utama yang menyerang tanaman kubis yang ditanam tumpang sari dengan refugia sawi hijau adalah hama Plutella xylostella dan Crocidolomia binotalis. Populasi hama P. xylostella pada tanaman kubis rendah berkisar rata-rata 0.002 – 0.067 larva/tanaman, sedangkan populasi hama C. binotalis tinggi dengan rata-rata berkisar 0.056 sampai 1.422 larva per tanaman. Perlu melestarikan parasitoid D. semiclausum untuk mengendalikan hama P. xylostella dan mencari solusi pengendalian hama C. binotalis yang ramah lingkungan untuk menghasilkan produksi kubis yang sehat. Keywords: Kubis, Sawi Hijau, Refugia, Hama, Parasitoid